An analysis of homogeneity and heterogeneity of elite sports systems in six nations - de Bosscher, V.; de Knop, P.; van Bottenburg, M. (International Journal of Sports Marketing & Sponsorship, 2009)
As a consequence of internationalisation, elite sports systems from different nations have been copied all over the world. Accordingly, in their search for the best pathway to success, elite sports systems and policies of different nations are converging to uniform models of elite sports development. But there is room for diversity. This paper explores to what extent elite sports policies in six nations (Belgium, Canada, Italy, the Netherlands, Norway and the UK) have become more homogeneous, and where differences emerge. The study uses a framework of nine policy areas or `pillars` that are identified as important sports policy factors leading to international sporting success. Data is collected through individual researchers in each nation, using semi-structured written questionnaires. 46 critical success factors are compared in order to detect the main similarities and variations in the sample nations for each pillar.